La vivencia de la educación virtual entre estudiantes y profesores universitarios en Ecuador: estudio de un caso (Investigaciones) - Barreto Zambrano, Lenin (2022)
In 2014, to make the learning of face-to-face degree students more flexible, the Technical University of Manabí implemented, without prior study, distance learning through virtual classrooms in certain subjects of the common core. The case study was used through interviews and discussion groups to know the strengths and weaknesses. The study’s objective is “to assess the performance of these courses and the results concerning the performance of students and teachers.” Among the main results, it is revealed that there are difficulties in functioning the environments, allowing students to prefer traditional environments. This study concludes that this modality does not arouse greater interest in students.